Gender Equity in the Role of Female Workers at PT Djarum Kudus: Amina Wadud's Perspective - Fiza Umi Latifah; Shofiyullah Muzammil (al-Afkar, Journal For Islamic Studies, 2026)
This research originates from the many cases of women who are always considered as inferior subjects in gender studies, this is influenced by the subjectivity of interpretation and understanding of the verses of the Koran. Women are confined as creatures of the household, not given the opportunity to express themselves, not given leadership opportunities, and underestimated as full human beings. The patriarchal culture of Islam, which has disenfranchised women, is to blame. Men and women are usually seen as members of different human races in Islamic culture. This study aims to re-examine the Qur'anic interpretation of women's rights and justice using Amina Wadud's theoretical foundation. It is from this foundation that Amina Wadud began to interpret the Quran in terms of feminism and gender justice. This research is a literature study with a qualitative approach that uses descriptive analysis. Data analysis is done through three stages: data reduction, data presentation and conclusion drawing. The results show that gender justice is a distinction between men and women, so women's experiences and perspectives must be valued equally with men. The Qur'an uses a person's level of piety as a benchmark to assess their value and dignity. Wadud said that, given the existence of gender-based leadership and duties, such reasoning is not suitable for a Muslim man and shows the low quality of his faith. Justice in this context refers to the consideration of both material and immaterial issues.